Analysis of the Completeness of Integrated Patient Progress Notes (CPPT) in Mental Health Care Medical Records at Prof. HB. Sa'anin Mental Hospital, Padang: - - Nasution, Nurhasanah; Mandia, Sayati (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2024)
Good healthcare services are not only provided to patients; they also require documentation containing patient information, known as medical records. Medical records are a comprehensive record of all information and services provided at a healthcare facility, from admission to discharge. These records are crucial and must be properly maintained and managed. One such record is the patient progress note, known as CPPT. Based on a preliminary study conducted through surveys and interviews at Prof. HB. Sa'anin Mental Hospital, incompleteness in the CPPT was still found. Therefore, the authors were interested in conducting research on the completeness of the CPPT, both quantitatively and qualitatively, in the mental health care medical records at Prof. HB. Sa'anin Mental Hospital, Padang City. The study was conducted in March 2024, using a quantitative descriptive method. The study results showed the highest score for identification review was 99% complete, and the lowest score for authentication review was 53% incomplete. The researchers recommended that the head of medical records immediately disseminate medical record guidelines and standard operating procedures (SOPs) for filling out medical records.